Answer:
B. y = 2x - 2
E.
![y + 4 = 2(x + 1)](https://img.qammunity.org/2022/formulas/mathematics/college/k5nhf4g4tsya2pl3tm16n99mbz3exhqrmc.png)
F.
![y - 6 = 2(x - 4)](https://img.qammunity.org/2022/formulas/mathematics/college/xmpga9hiusr95s7iqexfmu23kwi80zdldy.png)
Explanation:
The equation of the line can be found using either the point-slope equation or the slope-intercept equation.
✔️Equation of the line in point-slope using the slope and the coordinates of the point (4, 6):
Slope = m = change in y/change in x
Using (4, 6) and (-1, -4),
m = (-4 - 6)/(-1 - 4)
m = -10/-5
m = 2
Substitute m = 2, and (a, b) = (4, 6) into the point-slope equation form
![y - b = m(x - a)](https://img.qammunity.org/2022/formulas/mathematics/college/upstntzsxmt79uz5cksot1x3pcqn83y8u8.png)
Thus:
![y - 6 = 2(x - 4)](https://img.qammunity.org/2022/formulas/mathematics/college/xmpga9hiusr95s7iqexfmu23kwi80zdldy.png)
✔️Equation of the line in point-slope using the slope and the coordinates of the point (-1, -4):
Slope = m = 2
Substitute m = 2, and (a, b) = (-1, -4) into the point-slope equation form
![y - b = m(x - a)](https://img.qammunity.org/2022/formulas/mathematics/college/upstntzsxmt79uz5cksot1x3pcqn83y8u8.png)
Thus:
![y - (-4) = 2(x - (-1))](https://img.qammunity.org/2022/formulas/mathematics/college/qhsz2c0ttm8akypxvln7kgc1j1aojiyn32.png)
![y + 4 = 2(x + 1)](https://img.qammunity.org/2022/formulas/mathematics/college/k5nhf4g4tsya2pl3tm16n99mbz3exhqrmc.png)
✔️Equation of the line in slope-intercept form, y = mx + b
Where,
m = slope = 2
b = y-intercept = -2 (the point where the line intercepts the y-axis)
Thus, substitute m = 2 and b = -2 into y = mx + b
y = 2x + (-2)
y = 2x - 2